Cortical entrainment to speech produced by cochlear implant talkers and normal-hearing talkers - Raghavendra, Shruthi; Lee, Sungmin; Chun, Hyungi; Martin, Brett A.; Tan, Chin-Tuan (Frontiers in Neuroscience, 2022)
Cochlear implants (CIs) are commonly used to restore the ability to hear in those with severe or profound hearing loss. CIs provide the necessary auditory feedback for them to monitor and control speech production. However, the speech produced by CI users may not be fully restored to achieve similar perceived sound quality to that produced by normal-hearing talkers and this difference is easily noticeable in their daily conversation. In this study, we attempt to address this difference as perceived by normal-hearing listeners, when listening to continuous speech produced by CI talkers and normal-hearing talkers. We used a regenerative model to decode and reconstruct the speech envelope from the single-trial electroencephalogram (EEG) recorded on the scalp of the normal-hearing listeners. Bootstrap Spearman correlation between the actual speech envelope and the envelope reconstructed from the EEG was computed as a metric to quantify the difference in response to the speech produced by the two talker groups. The same listeners were asked to rate the perceived sound quality of the speech produced by the two talker groups as a behavioral sound quality assessment. The results show that both the perceived sound quality ratings and the computed metric, which can be seen as the degree of cortical entrainment to the actual speech envelope across the normal-hearing listeners, were higher in value for speech produced by normal hearing talkers than that for CI talkers. The first purpose of the study was to determine how well the envelope of speech is represented neurophysiologically via its similarity to the envelope reconstructed from EEG. The second purpose was to show how well the representation of speech for both CI and normal hearing talker groups differentiates in term of perceived sound quality.